Mathematics Learning Process Students Grade IX in Pandemic COVID-19 Era - Syahwal, Apriliani; Suradi; Rusli (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study aims to determine the process of learning mathematics online or e-learning during the Covid-19 pandemic in class XI students at a high school in Soppeng. This research uses descriptive qualitative research with a qualitative approach. The subjects in this study were compulsory mathematics teachers for class XI. Data collection techniques in this study use observation, interviews, and documentation. The results of the research show that the process of learning mathematics is carried out online, which consists of planning mathematics lessons, implementing learning, and evaluating learning carried out by teachers during the online mathematics learning process at the Covid-19 pandemic.